Experience with Congenital Adrenal Hyperplasia in Tripoli Children's Hospital, Libya - Abulgassem, Intisar; BenRajab, Faten (Journal of Diabetes and Endocrine Practice, 2022)
Congenital adrenal hyperplasia (CAH) denotes a group of autosomal recessive disorders. Its clinical spectrum varies from classical CAH (CCAH) to nonclassic CAH. It may be a simple virilizing form or salt-wasting type. The study described the clinical presentation, treatment modalities, and sequelae of CAH, including its effect on patient growth during long-term follow-up. A case series study was conducted on patients with CAH who attended and followed up in the Endocrine Clinic in Tripoli Children's Hospital from January 1, 2000 to December 31, 2018. The presentation and the last visit captured demographic and clinical features at the time of diagnosis, types of CAH (classical vs. nonclassical), investigations, treatment details, and height. All patients underwent biochemical testing and hormonal assay, including adrenocorticotropin hormone (ACTH), 17-hydroxyprogesterone (17-OHP), and plasma renin activity (PRA) levels before and after treatment. Fifty-eight patients were included; 38 (65.5.2%) were female, age at presentation in 94.8% ranged between 1 day and 10 years, with a mean age of 2.3 ± 1.1 years. Ambiguous genitalia was the presenting feature in 55.2 and 84% of total and female patients, respectively. Salt wasting was present in 37.9%. Of 32 female patients with ambiguous genitalia, only 11 (34.4%) out of them and 19% of all patients had a surgical correction. The mean and standard deviation of height at diagnosis was 78.327 + 31.070, and the last visit after treatment was 108.345 + 31.781. The relation between the date of birth and height throughout follow-up for those at last visit with age ranges from 13 to 18 years old, their mean and standard deviation of height was 135.650 + 29.286, and for patients who were less than13 years at last visit, the mean and standard deviation of height was 101.079 + 32.121; p-value = 0.003. The Z-scores were calculated and showed that about eight patients were positively above the average mean of the population. Biochemical disturbances were improved after treatment, including sodium, potassium, and glucose in CCAH type; p-value < 0.001. Hormonal findings included levels of ACTH, 17-OHP, and PRA; all levels were reduced with treatment; p-value < 0.001. In this single-center series, most of our patients with biochemical and hormonal abnormalities were normalized with hormonal replacement and limited surgical correction of females with ambiguous genitalia.
Keywords: CAH; classical CAH; nonclassical CAH; adrenal crisis; genital ambiguity